2013
DOI: 10.4271/2013-01-0274
|View full text |Cite
|
Sign up to set email alerts
|

Concept of “Temperature Swing Heat Insulation” in Combustion Chamber Walls, and Appropriate Thermo-Physical Properties for Heat Insulation Coat

Abstract: The aim of this work is to investigate the possibility of heat insulation by "Temperature Swing", that is temperature fluctuation, on combustion chamber walls coated with low-heat-conductivity and low-heat-capacity materials.Adiabatic engines studied in the 1980s, such as ceramic coated engines, caused constantly high temperature on combustion wall surface during the whole cycle including the intake stroke, even if it employed ceramic thermal barrier coating methods. This resulted in increase in NOx and Soot, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 10 publications
1
77
0
Order By: Relevance
“…Keywords : ICEs, Heat insulated coating, Wall heat transfer, Modeling, Thin-film thermocouple, PIV (Assanis and Badillo, 1987), ( Fujimoto et al, 2011), (Yamashita et al, 2012, (Kosaka et al, 2013) Initial wall temperature (K) 298…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keywords : ICEs, Heat insulated coating, Wall heat transfer, Modeling, Thin-film thermocouple, PIV (Assanis and Badillo, 1987), ( Fujimoto et al, 2011), (Yamashita et al, 2012, (Kosaka et al, 2013) Initial wall temperature (K) 298…”
Section: Introductionmentioning
confidence: 99%
“…In addition, non-dimensional velocity distribution in wall boundary layer was not changed drastically by wall temperature behavior. In terms of modeling under heat insulated condition, wall heat flux was able to be predicted well by wall heat transfer model taking into account of density change in wall boundary layer.Keywords : ICEs, Heat insulated coating, Wall heat transfer, Modeling, Thin-film thermocouple, PIV (Assanis and Badillo, 1987), ( Fujimoto et al, 2011), (Yamashita et al, 2012, (Kosaka et al, 2013) Initial wall temperature (K) 298Initial gas pressure Atmospheric Pressure (Han and Reitz, 1997)(Harada et al, 2017) Harada, Y., Uchida, K., Tanaka, T., Sato, K., Qianjin, Z., Fujimoto, H., Yamashita, H. and Tanahashi, M., Wall heat transfer of undeveloped turbulent flow in internal combustion engines, COMODIA2017 (2017), A204. …”
mentioning
confidence: 99%
“…This consideration is necessary especially in materials that contain low volumetric heat capacity which would allow fast changes in temperature, and low thermal conductivity which would enable a reduction in overall heat transfer and an increase in surface temperature during combustion and expansion. In both analytical (Wallace, Way, & Vollmert, 1979) (Morel, Fort, & Blumberg, 1985) (Anderson & Prakash, 1985) (Kosaka, et al, 2013) and experimental (Furuhama & Enomoto, 1987) (Harder & Anderson, 1988) (Aoki, et al, 2015) studies, a non-negligible swing in surface temperature throughout the engine cycle was observed with increasing insulation. This poses unique possibilities and challenges over the concept of a steady, elevated temperature and was fundamentally different from the net-zero heat transfer model with respect to the processes occurring in-cylinder.…”
Section: Temperature-swing Insulation In Literaturementioning
confidence: 95%
“…There has been considerable recent activity to minimize heat losses and improve engine efficiency through in-cylinder temperature-swing insulation (Kosaka, et al, 2013) (Kogo, et al, 2016) (Kumar & Nagarajan, 2012) (Hoffman, Lawler, Guralp, Najt, & Filipi, 2015). The capability for surface temperature swing is dictated in part by the intrinsic material properties of the material in contact with the gas.…”
Section: Literature Review Overviewmentioning
confidence: 99%
See 1 more Smart Citation